2022
DOI: 10.1093/hr/uhac254
|View full text |Cite
|
Sign up to set email alerts
|

Promoter replacement of ANT1 induces anthocyanin accumulation and triggers the shade avoidance response through developmental, physiological and metabolic reprogramming in tomato

Abstract: The accumulation of anthocyanins is a well-known response to abiotic stresses in many plant species. However, knowledge about the effects of excessive anthocyanin accumulation on light absorbance and photosynthesis is limited. Here, we addressed this question using a promoter replacement line of tomato constitutively expressing a MYB transcription factor (ANTHOCYANIN1, ANT1) that leads to anthocyanin accumulation. The genetic engineered ANT1 plants displayed traits associated with shade avoidance response: thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Anthocyanin accumulation is commonly restricted to the subepidermal cells and absent in the parenchymal cells of the mesocarp, mesophyll, and cortex. Substrate is likely to be available in these cells since the expression of specific transgenic MYB and bHLH transcription factors leads to high anthocyanin accumulation in the inner tissues of the tomato fruit (Butelli et al ., 2008; Cerqueira et al ., 2023). Therefore, other mechanisms should explain this “parenchymal recalcitrance”, a widespread phenomenon throughout the angiosperms (Chaves-Silva et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthocyanin accumulation is commonly restricted to the subepidermal cells and absent in the parenchymal cells of the mesocarp, mesophyll, and cortex. Substrate is likely to be available in these cells since the expression of specific transgenic MYB and bHLH transcription factors leads to high anthocyanin accumulation in the inner tissues of the tomato fruit (Butelli et al ., 2008; Cerqueira et al ., 2023). Therefore, other mechanisms should explain this “parenchymal recalcitrance”, a widespread phenomenon throughout the angiosperms (Chaves-Silva et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the ecological notion that anthocyanins are responsible for attracting pollinators and seed dispersers, they also play a protective role due to their antioxidant activity by scavenging reactive oxygen species (ROS) that otherwise could severely damage plant tissues (Buer et al ., 2010; Corso et al ., 2020). Furthermore, it has been suggested that anthocyanins form a protective barrier in plant tissues by absorbing the UV-B radiation potentially harmful to the photosynthetic machinery (Gould et al ., 2010; Cerqueira et al ., 2023). These properties make anthocyanins an important protective compound against environmental stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was found that loss-of-function mutations in the AN2 ortholog in wild tomato impair anthocyanin synthesis [314]. Overexpression of ANT1 in tomatoes enriched the anthocyanins in leaves, contributing to more intense light absorption in the blue and red spectrum [315]. However, introducing knockout mutations into the AN2like gene rather than ANT1 (ANTHOCYANIN) essentially eliminates the accumulation of anthocyanins [316][317][318].…”
Section: Abiotic Ripening Factorsmentioning
confidence: 99%
“…Additionally, it was found that loss-of-function mutations in the AN2 ortholog in wild tomato impair anthocyanin synthesis [146]. Overexpression of ANT1 in tomatoes enriched the anthocyanins in leaves, contributing to more intense light absorption in the blue and red spectrum [147]. However, introducing knockout mutations into the AN2-like gene rather than ANT1 (ANTHOCYANIN) essentially eliminates the accumulation of anthocyanins [149,150].…”
Section: Abiotic Ripening Factorsmentioning
confidence: 99%